Using nominal group technique to select an HIV status disclosure decision aid for adaptation in Georgia - Tamar Zurashvili; Mariam Pashalishvili; Akaki Abutidze; Fiona Evelene; Nino Chikhladze; Mamuka Djibuti (PLoS ONE, 2026)
Introduction HIV status disclosure decision-making is a complex process influenced by stigma, relationship dynamics, and anticipated social consequences. Although decision aids can support individuals in navigating such decisions, no disclosure decision-support interventions have been adapted for use in the Georgian context. This study aimed to identify and prioritize an existing evidence-based intervention for adaptation to support HIV disclosure decision-making among people living with HIV (PLWH) in Georgia. Methods We used the Nominal Group Technique (NGT), a structured consensus method, to elicit and prioritize stakeholder perspectives. Two separate NGT sessions were conducted with HIV care providers (n = 12) and PLWH (n = 10), followed by a joint session to reach consensus. Prior to the sessions, nine evidence-based disclosure decision-support interventions from HIV, mental health, and substance use fields were identified through a desk review and grouped into session-based, paper-based, and digital formats. Participants generated ideas, discussed advantages and limitations, and ranked intervention formats and specific interventions. Descriptive content analysis was used to summarize discussion themes. Results Providers prioritized digital interventions, emphasizing accessibility and scalability, whereas PLWH preferred session-based interventions, highlighting the importance of trust, individualized support, and peer involvement. Within these formats, providers favored a structured digital program, while PLWH selected an individual session-based intervention focused on disclosure to family members. Adaptation priorities included incorporating peer educators, addressing disclosure to different social and healthcare contexts, and including locally relevant content on legal issues, treatment adherence, and available support services. In the joint session, consensus was reached to prioritize the intervention selected by PLWH. Conclusions This study identified a priority disclosure decision-support intervention for adaptation to the Georgian context, emphasizing the importance of patient-centered and contextually tailored approaches. Future research will focus on adapting the selected intervention and identifying appropriate implementation strategies to support pilot testing and integration into HIV care services.